Revisión sobre factores a considerar en la implementación de un sistema de gestión de calidad en pymes colombianas (2021)
Current business models demand that organizations guarantee the fulfillment of basic requirements in their products or services, to ensure quality and customer satisfaction. The implementation of a quality management system facilitates the improvement and strengthening of the processes that contribute to the fulfillment of quality requirements. The objective of this document is to review factors to consider in the implementation of a quality management system in Colombian SMEs. The study describes the context of Colombian SMEs, the key factors that influence the achievement of the results expected by quality management systems. The results obtained indicate that it is important to consider factors such as: organizational learning, strategy, structure, organizational culture and organizational individual, in the processes of implementation of quality management systems.